Oncogenic human papilloma virus and cervical pre-cancerous lesions in brothel-based sex workers in India - Kamalesh Sarkar; Swati Bhattacharya; Subhasish Bhattacharyya; Soma Chatterjee; Aiyel Haque Mallick; Sekhar Chakraborti; Debashree Chatterjee; Baishali Bal (Elsevier, 2008)
Summary: A community-based cross-sectional study was conducted in brothel-based sex workers of West Bengal, Eastern India, to determine their oncogenic human papillomavirus (HPV) status and the presence of pre-cancerous lesions. A total of 229 sex workers from three districts of West Bengal participated in the study. All the study participants were interviewed with the aid of a pre-tested questionnaire to determine their sociodemographics, risk behaviour and risk perceptions after obtaining informed verbal consent. The interview was followed by collection of cervical cells from all participants using a disposable vaginal speculum and cervical cytobrush. Oncogenic HPV DNA was detected by real-time polymerase chain reaction (PCR). A simultaneous Papanicolaou test ('Pap smear') was performed to detect cervical cytological abnormalities. Overall, the prevalence of oncogenic HPV was found to be 25% (58/229) among the studied population. A subset (n = 112) of the sample was tested separately to determine the existence and magnitude of HPV genotypes 16 and 18. The results showed that genotype 16 was prevalent in 10% (11/112), genotype 18 in 7% (8/112) and both genotype 16 and 18 in 7% (8/112). The HPV prevalence rate showed a decreasing trend with age, being 71.4% in the 10-19 years age group, 32.3% in the 20-29 years age group, 18.3% in the 30-39 years age group and 2.5% in the ≥40 years age group (statistically significant differences, P ≤ 0.00001). Considering the duration of sex work, oncogenic HPV prevalence was found to be 55% (n = 21) and 19% (n = 35) in sex workers with a sex working duration of ≤1 year and >1 year, respectively. This difference was found to be statistically significant both by univariate and multivariate analysis. In this study, it was observed that sex workers with an average number of daily clients of six or more had an HPV prevalence of 67% (n = 6), those with four to five clients had a prevalence of 45% (n = 9), those with two to three clients had a prevalence of 30% (n = 34) and those with one or less clients had a prevalence of 10% (n = 9) (statistically significant differences, P = 0.00003). Multivariate analysis showed a statistical association only with a duration of sex work of ≤1 year [odds ratio (OR) = 3.3; 95% confidence interval (CI) 1.4-7.6] and daily income of Rupees (Rp) ≥101 (OR = 2.5; 95% CI 1.3-5). Regarding pre-cancerous lesions, 2 of 229 sex workers showed the presence of a low-grade squamous intraepithelial lesion along with high-risk HPV. Thus, 1% of the studied population suffer from a pre-cancerous lesion caused by high-risk HPV. This study concludes that young sex workers are particularly vulnerable to high-risk HPV, similar to human immunodeficiency virus (HIV). The observation of older sex workers relatively free from HPV supports the view of acquired immunity against HPV, which needs to be studied in-depth further. There is a need for a suitable community-based intervention programme targeted towards sex workers, with special reference to younger sex workers, for control and prevention of HPV and cervical cancer. Vaccination against HPV for newly entrant sex workers may be an important component for a successful intervention programme. Keywords: Human papillomavirus, Oncogenic HPV, Sex workers, India, Risk factors, Cervicitis, Cervical pre-cancerous lesion, STI